Suspensórios: inscrições épicas em palhaços, de Timochenco Wehbi - Rodrigues, Aurélio Costa (2016)
The purpose of this work is to look at the theatrical text of a little known author: Timochenko Wehbi (1946-1986). Because of this, the first part of this paper offers an overview of the author and his production. In the second part, we present the main ideas about the piece Clowns, so that it is possible to glimpse the general construction of the plot and the constitution of the characters. In the third part, we point out the possible links of his writing with epic elements of Brechtian bases. Timochenko Wehbi wrote his texts in the 1970s-80s, within a historical period with demarcated characteristics, and the piece Clowns is from the beginning of 1970, ie, his beginning as a writer. From the very first, he wrote from a foundation that we could treat as sociologically oriented, first because of his academic background - he was a sociologist and teacher in the field - which seems to have determined his interest in certain characters and the way of Treat them. Second, his interest in theater sociology and by Brecht tends to reinforce certain inclinations and direct elements that are inscribed in his texts, making possible to connect his creation with postulates of the Brechtian epic. We must emphasize that there are no studies on the author's text, which obliges us to deal with his production without starting from previous formulations that can serve as a consistent critical basis, except for newspapers of the period, which are generally quite generic